2017
DOI: 10.1111/cen3.12398
|View full text |Cite
|
Sign up to set email alerts
|

Active form of vitamin D directly protects the blood–brain barrier in multiple sclerosis

Abstract: Objectives The active form of vitamin D, 1a, 2 D 3 ), is reported to have protective effects for multiple sclerosis (MS), but the precise mechanisms of this effect on MS remain unclear. We hypothesized that 1a,25-(OH) 2 D 3 has protective effects on the blood-brain barrier (BBB) in MS. Methods The expression of vitamin D receptor in a human brain microvascular endothelial cell line (HBMEC) was examined. The effects of 1a,25-(OH) 2 D 3 on HBMEC after stimulation with tumor necrosis factor-a were observed. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…In addition, it is interesting to notice that vitamin D receptor (VDR) is localized not only in the nuclei of interfollicular epidermal cells but also in HF cells and human brain microvascular endothelial cells. 22 As reported by Visconti et al, 23…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In addition, it is interesting to notice that vitamin D receptor (VDR) is localized not only in the nuclei of interfollicular epidermal cells but also in HF cells and human brain microvascular endothelial cells. 22 As reported by Visconti et al, 23…”
Section: Discussionmentioning
confidence: 71%
“…In addition, it is interesting to notice that vitamin D receptor (VDR) is localized not only in the nuclei of interfollicular epidermal cells but also in HF cells and human brain microvascular endothelial cells . As reported by Visconti et al, VDR influences the expression and functions of tight junction (TJ) proteins: altered VDR expression is apparently associated with TJ s defects, with consequent cutaneous barrier alterations.…”
Section: Discussionmentioning
confidence: 90%
“…Some studies have shown that corticosteroids increase the expression of claudin-5 and strengthen the barrier property [25]. Our data demonstrated that fingolimod or the active form of vitamin D, which are used to treat multiple sclerosis (MS), enhance barrier function via the upregulation of claudin-5 and reduction in the VCAM-1 expression [26,27].…”
Section: Treatment For Bbb Disruption In Neuroinflammatory Diseasesmentioning
confidence: 65%
“…To the best of our knowledge, BBB stabilization by 1,25-VitD3 at the level of the spinal cord in EAE mice is being described here for the first time. However, it remains important to remember that many other molecules are part of this barrier and that their expression could also be modulated by 1,25-VitD3, such as claudins and occludin (Stamatovic et al, 2016;Takahashi et al, 2017). Interestingly, the stabilization of this barrier coincided with a clear accumulation of MOG-reactive cells at the draining lymph nodes, which was detected by the increased production of proinflammatory cytokines by these cells in the presence of MOG.…”
Section: Discussionmentioning
confidence: 98%
“…Kruskal-Wallis, Dunn's test *p < 0.05. could contribute to the protective effect of vitamin D. BBB stabilization by 1,25-VitD3 was initially described in a mouse brain endothelial cell culture model by Won et al (2015). More recently, using human endothelial cells, Takahashi et al (2017), observed that these cells expressed VDR and that their contact with 1,25-VitD3 decreased permeability by reducing vascular cell adhesion molecule-1 expression and restoring the zonula occludens-1 and claudin-5. Since the tight junction protein ZO-1 controls endothelial adherens junction, cell-cell tension, angiogenesis, and barrier formation (Tornavaca et al, 2015), we also evaluated ZO-1 mRNA expression in the lumbar spinal cord.…”
Section: Discussionmentioning
confidence: 99%